1976
DOI: 10.1039/dt9760001232
|View full text |Cite
|
Sign up to set email alerts
|

Cationic low-spin bis[1,2-bis(dialkylphosphino)ethane]iron(II) complexes

Abstract: Cationic Low-spin Bis[l,2-bis(dial kylphosphino)ethane] iron(ir) Complexes tBy J o h n M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

1976
1976
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…This also applies to the corresponding dppe system [FeH(N 2 )(dppe) 2 ] + ( 1b ), which even forms in THF by reaction of the five‐coordinate precursor [FeH(dppe) 2 ]BPh 4 with air 58, 59. The five‐coordinate complex [FeCl(depe) 2 ] + , in contrast, is extremely oxygen sensitive in solution 64. These remarkable differences in reactivity are correlated with different electronic ground states that we have determined by a combination of magnetic susceptibility measurements, various spectroscopic methods, and DFT calculations.…”
Section: End‐on Terminal Coordinationmentioning
confidence: 98%
“…This also applies to the corresponding dppe system [FeH(N 2 )(dppe) 2 ] + ( 1b ), which even forms in THF by reaction of the five‐coordinate precursor [FeH(dppe) 2 ]BPh 4 with air 58, 59. The five‐coordinate complex [FeCl(depe) 2 ] + , in contrast, is extremely oxygen sensitive in solution 64. These remarkable differences in reactivity are correlated with different electronic ground states that we have determined by a combination of magnetic susceptibility measurements, various spectroscopic methods, and DFT calculations.…”
Section: End‐on Terminal Coordinationmentioning
confidence: 98%
“…The synthesis of [FeCl(N 2 )(depe) 2 ](BPh 4 ) (2) has been performed according to a procedure modified from the literature [13,15] a) The missing coordinates are generated by reflections.…”
Section: Sample Preparation and Isotopic Substitutionmentioning
confidence: 99%
“…Thus, the complex [FeH(dppe) 2 ] ϩ in a THF solution or in the solid state picks up N 2 from air, leading to [FeH(N 2 )(dppe) 2 ] ϩ [13,14]. A methanolic solution of [FeCl(depe) 2 ] ϩ , on the other hand, is extremely sensitive towards oxidation [13,15]. In order to understand these drastic differences in reactivity between otherwise identical hydrido and halogeno complexes, we started an investigation of the five-coordinate fragments [FeX(depe) 2 ] ϩ , Xϭhalide and hydride, by X-ray crystallography and spectroscopy (UV/Vis absorption, Mössbauer).…”
Section: Introductionmentioning
confidence: 99%
“…Our experiments showed that two equivalents of the larger diphosphine dcpe cannot bind to FeCl2 to form "FeCl2(dcpe)2" presumably because they create too much steric crowding around the metal center (formation of complexes of the type FeCl2(L)2 has been previously shown for smaller ligands L = dmpe and depe). 13 Even with heating, the only product from the reaction of FeCl2 and two or more equivalents of dcpe is the known species FeCl2(dcpe). 14 Nonetheless, we found that the reaction of paramagnetic FeCl2(dcpe) with two equivalents of NaBEt3H and one additional equivalent dcpe successfully yielded the diamagnetic, bis-ligated species cis-FeH2(dcpe)2 (1) as a pale yellow powder in 59% yield (Scheme 2).…”
mentioning
confidence: 99%